Import-export nell’area del Canale d’Otranto in etá tardo-ellenistica. L’evidenza delle ceramiche fini e dei contenitori da trasporto da Orikos (Valona-Albania) e da Muro Tenente (Brindisi-Italia) - De Mitri, Carlo (Rei Cretariae Romanae Fautorum Acta, 2022)
Study of the pottery found in recent excavations at Muro Tenente (Brindisi, Italy) and Orikos (Vlorë, Albania) provides an opportunity to add new data to the geographical and cultural framework of their localities, and to compare the pottery found on the opposing shores of the Strait of Otranto in the Late Hellenistic period. Analysis of the fine wares from the two sites shows the predominance of local productions over imports and highlights common characteristics on either side of the strait.